Low effect of young afforestations on bird communities inhabiting heterogeneous Mediterranean cropland - Sánchez-Oliver,Juan S.; Rey Benayas,José M.; Carrascal,Luis M. (PeerJ, 2015)
Afforestation programs such as the one promoted by the EU Common Agricultural Policy have spread tree plantations on former cropland. These afforestations attract generalist forest and ubiquitous species but may cause severe damage to open habitat species, especially birds of high conservation value. We investigated the effects of young (<20 yr) tree plantations dominated by pine P. halepensis on bird communities inhabiting the adjacent open farmland habitat in central Spain. We hypothesize that pine plantations located at shorter distances from open fields and with larger surface would affect species richness and conservation value of bird communities. Regression models controlling for the influence of land use types around plantations revealed positive effects of higher distance to pine plantation edge on community species richness in winter, and negative effects on an index of conservation concern (SPEC) during the breeding season. However, plantation area did not have any effect on species richness or community conservation value. Our results indicate that the effects of pine afforestation on bird communities inhabiting Mediterranean cropland are diluted by heterogeneous agricultural landscapes.
Keywords: Conservation status; Distance effects; Land use types; Pine plantations; Species richness; CAP